Strategi Penawaran dalam Industri Konstruksi (Studi Kasus di Layanan Pengadaan Secara Elektronik, Kota Bandung) - Hakas Prayuda, Mandiyo Priyo , (Jurnal Semesta Teknika, 2013)
The aims of this research are to calculate the value of mark-up using bidding strategy approach and to determine the best bidding strategy to win a tender with the optimum mark-up value and the optimum profit. The data being used in this research are auction data that have been completed in 2010-2012 at LPSE Bandung using statistical approach namely discrete multi distribution, normal multi distribution, and single normal distribution. Bidding strategy methods being used are Friedman Method, Gates Method, and Ackoff & Sasieni Method. The Friedman Method can generate an optimum mark-up of 10% with expected profit of -0.0014, an optimum mark-up of -9% with expected profit of -0.0003, and an optimum mark-up of -1%  with expected profit -0.0004 for discrete multi-distribution, multi-normal distribution, and  single normal distribution, respectively. The Gates Methods can produce an optimum mark up of 6% with expected profit of 1,5000, an optimum mark up of 5% with expected profit 0.0097, and an optimum mark up of 6% with expected profit 1.2888 for discrete multi distribution, multi-normal distribution, and single normal distribution, respectively. While the Ackoff & Sasieni Methods can generates an optimum mark-up of -2%  with expected profit -0.0003, an optimum mark-up of  1% with expected profit for 0,0013 for discrete multi distribution, and for both multi and single normal distributions, respectively.